Study on adaptive thermal comfort model and behavioral adaptation in naturally ventilated residential buildings, Jimma Town, Ethiopia - Chali, Yadeta (2023)
Ethiopia boasts abundant untapped energy resources, yet access to electricity remains limited (30%), with frequent and prolonged outages. Research on occupant thermal comfort in Ethiopia remains limited as well. This study aimed to investigate comfort temperature, adaptive models, and behavioral adaptations in naturally ventilated residential buildings in Jimma town, Ethiopia. Our thermal comfort field survey involved 870 occupants from 104 houses, generating 5220 datasets between February and September 2020. Indoor environments were simultaneously measured using handheld digital instruments. Notably, the subjects lacked electrical fans, space heaters, or air-conditioners, relying instead on charcoal and plant residue for cooking and heating.Overall, only 56.2% of subjects felt comfortable within the thermal sensation scale's defined band, while 70.9% preferred either warmer or cooler environments, and 63.4% accepted their environments. The mean comfort temperature was 23.3˚C ± 3.44 based on all data. Our adaptive model predicted a 1.82 K perturbation in outdoor running mean temperature, resulting in a unit change in indoor comfort temperature. Significant occupant behavioral adaptation through operable environmental controls, clothing choices, and activity levels was observed. Our model is essential for building simulation in Ethiopia, emphasizing the need for an Ethiopian adaptive standard. Given the limited modern energy sources, understanding low-energy thermal comfort and human adaptation becomes vital for sustainable living conditions.